The genus Crassolabium Yeates, 1967 (Nematoda, Dorylaimida): A monographic study - Peña Santiago, Reyes (Trabajos monográficos de Nematología, 2014)
This is a contribution devoted to describe the diversity of the genus Crassolabium, an interesting, wordwide distributed, dorylaimid nematode taxón, whose controversial taxonomy during the time never made the subject of any monographic research. General morphology and taxonomy of the genus are treated in detail, and its 33 valid species are describe on the base of a comprehensive compilation of available literatura. This work represents a modest trial to rescue the tradition of our "magisters" in the study of dorylaims.